School inequalities, tools to evaluarte them, and the study of the production processes. - Rochex, Jean-Yves (Profesorado, Revista de Currículum y Formación del Profesorado, 2015)
The article presents the results of those elements, not only of what is known about educational inequality and its evolution from the work of the sociology of education in the years 1960-1970, but also as tools of measurement and lines of thought with which we try to understand and better understand its dimensions and production processes. Data on inequalities in access to different levels of training or qualifications, but also to acquire knowledge and skills at national or international level are examined not only. It also focuses on educational inequalities between students belonging to different social classes, as well as gender inequalities, territorial inequalities and "context effects", as well as the most visible changes, paradoxes and contradictions through which they are reproduced and social and educational processes are renewed in the production of inequalities in access to knowledge and training.